Millennial Leaders and Worker Loyalty: The Influence of Leadership Style on Worker Loyalty of PT Xyz's Production Operations Division - Anwar Rifai; Bobby W Saputra (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of millennial leadership style on employee loyalty in the Production Operations Division of PT XYZ, an energy company in the oil and gas sector. Employing a quantitative approach through simple linear regression, the study involved 68 respondents, including production operators and laboratory technicians. The millennial leadership style was measured using six key indicators, while employee loyalty was assessed through f indicators reflecting affective commitment and organizational attachment. The statistical analysis reveals that millennial leadership style has a strong and significant effect on employee loyalty, with a coefficient of determination (R²) of 0.765. This means that 76.5% of the variation in loyalty is explained by leadership factors. The most influential indicators are decision-making ability and emotional control, both correlating at 0.66. Open communication and a sense of responsibility were also highly valued by employees. Workers expressed strong loyalty when led by empathetic, supportive, and communicative leaders. Conversely, the absence of such leadership increased the risk of turnover intentions. This study concludes that effective millennial leadership significantly enhances employee loyalty and offers protective effects against workforce turnover. Thus, a leadership approach rooted in empathy, collaboration, and participative management is essential for fostering emotional bonds and long-term organizational sustainability.